2012
DOI: 10.1371/journal.pone.0041501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvants on Responses to Skin Immunization by Microneedles Coated with Influenza Subunit Vaccine

Abstract: Recent studies have demonstrated the effectiveness of vaccine delivery to the skin by vaccine-coated microneedles; however there is little information on the effects of adjuvants using this approach for vaccination. Here we investigate the use of TLR ligands as adjuvants with skin-based delivery of influenza subunit vaccine. BALB/c mice received 1 µg of monovalent H1N1 subunit vaccine alone or with 1 µg of imiquimod or poly(I:C) individually or in combination via coated microneedle patches inserted into the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 50 publications
(52 reference statements)
3
38
1
1
Order By: Relevance
“…In agreement with this observation, multiple intradermal immunization studies using different administration methods have shown added effects of different Toll-like receptor (TLR) agonists based adjuvants [16,45]. In our study, co-delivery of OVA and the TLR3 agonist poly(I:C) in PLGA nanoparticles, led to protective cellular immune responses to rLM-OVA.…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with this observation, multiple intradermal immunization studies using different administration methods have shown added effects of different Toll-like receptor (TLR) agonists based adjuvants [16,45]. In our study, co-delivery of OVA and the TLR3 agonist poly(I:C) in PLGA nanoparticles, led to protective cellular immune responses to rLM-OVA.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, TLR7 appeared to play some role in the protection of the vaccine day Ϫ3 group because the removal of ssRNA from the vaccine day Ϫ3 group with RNase abolished the protective response of the vaccine day Ϫ3 group but not that of the VCI day Ϫ3 group. Weldon et al previously showed that imiquimod can enhance IFN-␥, leading to a Th1 cellular immune response and isotype switching, which resulted in a specific increase in the level of IgG2a (40). However, in our study, the increase in the pulmonary IFN-␥ level was much smaller in the VCI day Ϫ3 group than in the vaccine day Ϫ3 group, together with the increase in the total serum IgG, IgG2a, and IgG2b levels.…”
Section: Discussioncontrasting
confidence: 78%
“…Body weight and percent survival were monitored daily for 14 days after virus inoculation. A body weight loss of 30% was set as the humane endpoint (8,17). At 7, 14, and 28 days postinfection (dpi), blood samples were taken, and serum samples were stored at Ϫ80°C in aliquots for subsequent testing.…”
Section: Virusesmentioning
confidence: 99%